Dietary Iron Repletion following Early-Life Dietary Iron Deficiency Does Not Correct Regional Volumetric or Diffusion Tensor Changes in the Developing Pig Brain - Mudd, Austin T.; Fil, Joanne E.; Knight, Laura C.; Dilger, Ryan N. (Frontiers in Neurology, 2018)
Background: Iron deficiency is the most common micronutrient deficiency worldwide and children are at an increased risk due to the rapid growth occurring during early life. The developing brain is highly dynamic, requires iron for proper function, and is thus vulnerable to inadequate iron supplies. Iron deficiency early in life results in altered myelination, neurotransmitter synthesis, neuron morphology, and later-life cognitive function. However, it remains unclear if dietary iron repletion after a period of iron deficiency can recover structural deficits in the brain. Method: Twenty-eight male pigs were provided either a control diet (CONT; n = 14; 23.5 mg Fe/L milk replacer) or an iron deficient diet (ID; n = 14; 1.56 mg Fe/L milk replacer) for phase 1 of the study, from postnatal day (PND) 2 until 32. Twenty pigs (n = 10/diet from phase 1) were used in phase 2 of the study from PND 33 to 61, all pigs were provided a common iron sufficient diet, regardless of their early-life dietary iron status. All pigs remaining on study were subjected to magnetic resonance imaging at PND 32 and again at PND 61 using structural imaging sequences and diffusion tensor imaging to assess volumetric and microstructural brain development, respectively. Data were analyzed using a 2-way ANOVA to assess the main and interactive effects of early-life iron status and time. Results: An interactive effect was observed for absolute whole brain volumes, in which whole brain volumes of ID pigs were smaller at PND 32 but were not different than CONT pigs at PND 61. Analysis of brain region volumes relative to total brain volume indicated interactive effects (i.e., diet × day) in the cerebellum, olfactory bulb, and putamen-globus pallidus. Main effects of early-life iron status, regardless of imaging time point, were noted for decreased relative volumes of the left hippocampus, right hippocampus, thalamus, and increased relative white matter volume in ID pigs compared with CONT pigs. Diffusion tensor imaging indicated interactive effects for fractional anisotropy (FA) in the whole brain, left cortex, and right cortex. Main effects of early-life iron status, regardless of imaging time point, were observed for